2011
DOI: 10.1186/1472-6920-11-33
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety education for undergraduate medical students: a systematic review

Abstract: BackgroundTo reduce harm caused by health care is a global priority. Medical students should be able to recognize unsafe conditions, systematically report errors and near misses, investigate and improve such systems with a thorough understanding of human fallibility, and disclose errors to patients. Incorporating the knowledge of how to do this into the medical student curriculum is an urgent necessity. This paper aims to systematically review the literature about patient safety education for undergraduate med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
1
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(120 citation statements)
references
References 17 publications
3
104
1
10
Order By: Relevance
“…All members of multiprofessional health care teams, including students, should be capable of identifying risk situations, providing notification of errors and adverse events in a systematic manner, analyzing the system and disclosuring the occurrence of such events to patients and family members, thereby contributing to promote safe and quality care, as they have the proper training, orientation and support. [6][7] Standard precautions were established in 1996 by the Centers for Disease Control and Prevention in the USA to be adopted during the care of all patients, regardless their diagnosis. 8 The recommended measures include hand hygiene and the use of individual protection equipment.…”
Section: Discussionmentioning
confidence: 99%
“…All members of multiprofessional health care teams, including students, should be capable of identifying risk situations, providing notification of errors and adverse events in a systematic manner, analyzing the system and disclosuring the occurrence of such events to patients and family members, thereby contributing to promote safe and quality care, as they have the proper training, orientation and support. [6][7] Standard precautions were established in 1996 by the Centers for Disease Control and Prevention in the USA to be adopted during the care of all patients, regardless their diagnosis. 8 The recommended measures include hand hygiene and the use of individual protection equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Small group learning has been the most commonly used teaching model in patient safety education. 2,6 This is most likely due to it being a less resource-intensive method, with patient safety workshops, tutorials or problem-based learning cases easily inserted into existing curricula. Although this method is quite effective for use in a single discipline, it has been shown that multi-disciplinary small group workshops that are implemented toward the end of a health care professional degree program can be of greater benefit, particularly enabling better teamwork and communication.…”
Section: Introductionmentioning
confidence: 99%
“…4 To date, the delivery of patient safety education has centered on didactic methods of teaching, 2 and although this method is useful in increasing knowledge, it appears to be less effective in changing the attitudes and practices of students and health care professionals. As more systems-based approaches to managing errors in care have been adopted, so have the pedagogical methods in teaching students, graduates and health care professionals about safety and quality improvement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,12,13,25 Where formal educational activities were described, they were mostly single modules rather than embedded curricula. 26 There was also relatively little information about the content and delivery of patient safety teaching, although some studies reported that there was little in the way of interprofessional patient safety teaching.…”
Section: -24mentioning
confidence: 99%